Particle-Reinforced Aluminium Solid Self-piercing Rivets for Joining Aluminium Alloy Sheets - Koch, Steffen; Weber, Joshua; Meschut, Gerson; Stadelmann, Claudia; Böhm, Wolfgang; Merklein, Marion (Proceedings in Engineering Mechanics)
The use of aluminium materials in the structural and bodywork areas of assemblies has proven to be a targeted option for lightweight design. How-ever, the reliable and cost-efficient joining of aluminium components remains a challenge. Mechanical joining methods, such as riveting, are frequently used in the automotive and aerospace construction industries. Rivets are made from heat-treated steels. Compared to steel, the use of aluminium materials for fasten-ers offers several advantages in terms of joining properties, particularly in terms of recyclability, corrosion resistance and reduced weight of the joined structure. Additionally, the manufacturing process is shorter since aluminium fasteners do not require coating. However, aluminium rivets can often not be used due to the insufficient mechanical strength of the fastener material in relation to the joining component materials. This study systematically investigates the requirements for using solid alu-minium self-piercing rivets. The influence of rivet geometry adjustments on the joint quality is analysed using numerical simulation. The results are used to derive and evaluate an optimised rivet geometry for joining pure aluminium sheets. On this basis, solid self-drilling rivets with optimised geometry are manufactured from particle-reinforced aluminium produced in a continuous extrusion process by machining. The integration of particles increases the material’s strength. Exper-imental tests are conducted to evaluate the use of optimised solid self-piercing rivets. The quality-relevant parameters are determined and evaluated based on macrographs of the joints.
Keywords: Solid self-piercing riveting cdot particle-reinforced aluminium cdot continuous powder extrusion cdot Joining technology cdot Rivet geometry cdot lightweight design

Adaptive Coaxial Concrete Rheometer (ACCR): Honest Rheological Measurements and Corrections - Jesinghausen, Steffen; Schmid, Hans-Joachim (Opus Fluidum Futurum—Rheology of Reactive, Multiscale, Multiphase Construction Materials)

Metamorphosen als Akte weiblicher Handlungsmacht in Texten von Brigitte Kronauer, Han Kang und Camilla Grudova - Öhlschläger, Claudia (Geschlecht und Macht (feministische studien))

Zu Fotografien der Berliner Künstlerin Cihan Çakmak - Öhlschläger, Claudia (Geschlecht und Macht (feministische studien))

Geschlecht und Macht - Öhlschläger, Claudia; Riegraf, Birgitt (Geschlecht und Macht (feministische studien))

Geschlecht und Macht (feministische studien)

Diffeomorphism groups of compact locally polyhedral manifolds - Jakob, Johanna

Beyond Security: A Qualitative Study of Cyber Resilience Across the Software Development Lifecycle in German Organisations - Taaibi, Samira; Kahraman, Emanuel; Berg, Kevin; Dziwok, Stefan (ECIS 2026 Proceedings)
As digital products become increasingly embedded in organisational operations, cyber resilience – the ability to anticipate, withstand, recover from and adapt to cyber disruptions – has become essential. This paper investigates how professionals in German organisations interpret cyber resilience within the software development lifecycle and how socio-technical factors influence its implementation. Drawing on the MITRE Cyber Resiliency Engineering Framework for data collection and coding on Socio-Technical Systems as an interpretive lens, the study adopts a qualitative approach based on semi-structured interviews with 14 professionals across five organisations. The findings reveal a pronounced socio-technical imbalance: while technical measures centred on anticipate and withstand are comparatively established, the corresponding social factors – shared understanding, dedicated responsibility structures, and systematic learning – remain underdeveloped. These conditions are compounded by resource constraints and the absence of strategic prioritisation. Six exploratory hypotheses capture these patterns and offer empirically grounded starting points for future research on product-level cyber resilience.
Keywords: Cyber Resilience; Software Development Lifecycle; Qualitative Study; Cyber Resiliency Engineering Framework

„When does a man become a monster?“ Odysseus’ fluide Identität in Jorge Rivera-Herrans’ EPIC – The Musical - Peine, Sara (Wasser Wesen Wandel. Fluidität in (mehr-als-)literarischen Medien)

What is Participatory Digital Democracy? - Friesch, Kevin; Fuchs, Christian; Museba, Joel (The Communication Review)

Sportentwicklungsplanung - Meier, Heiko; Riedl, Lars; Kukuk, Marc (Grundwissen Sportsoziologie. Mit eLearning-Kurs)

Von Stilen, Quellen und Bildern - Siemoneit, Johannes Gabriel (Artes Renascentes)

Sitografia - Siemoneit, Johannes Gabriel (Artes Renascentes)

Rewiring the aging brain: exergaming modulates brain complexity in older adults - Piskin, Daghan Yüksel; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Frontiers in Aging Neuroscience)
Introduction Age-related changes in brain signal complexity are associated with cognitive decline and reduced neural adaptivity in older adults. Exergaming offers a promising prophylactic intervention combining physical and cognitive training. The aim of the present study was to assess how exergaming alters the temporal trajectory of brain signal complexity at rest and during gameplay in older adults. Methods Twenty-eight healthy older adults participated in a 4-week exergaming intervention. Electroencephalography was recorded using 64 electrodes at rest (pre- and post-intervention) and during exergaming (pre-, mid-, and post-intervention). Brain signal complexity was quantified using multiscale entropy across 64 time scales on preprocessed signals. Results Post-intervention resting-state analysis revealed significant reductions at fine and increases at coarse scales in frontal, central, and posterior entropy. During gameplay, entropy declined widespread by mid-intervention, particularly at coarse scales over frontal, central and temporal regions. From mid- to post-intervention, the decline narrowed leaving a net pre-to-post reduction concentrated at coarse scales in these regions. Discussion Resting-state changes indicated a shift toward a younger brain profile, characterized by a transition from age-related increases in local processing to enhanced distributed processing, which may potentially mitigate the rise in neural modularity associated with aging. During gameplay, brain signal complexity decreased in week 2, followed by a modest change by week 4, consistent with the framework in which complexity initially streamlines and then adjusts toward a task-specific optimum. These findings suggest that exergaming can beneficially modulate brain complexity in older adults, offering the potential to reduce age-related neural decline and support healthy brain aging.

Thermodynamic Properties of Tetramethoxysilane - Fiedler, F.; Baumhögger, Elmar; Kruse, Simon; Lemmon, E. W.; Kasper, Tina; Thol, M. (International Journal of Thermophysics)
Abstract A fundamental equation of state for tetramethoxysilane (TMOS) is developed based on the available experimental data. In addition, new density and speed of sound measurements were performed specifically for this work to improve the database. Owing to the limited overall data set, additional thermodynamic properties were analyzed to support the fitting procedure and ensure physically consistent behavior. Modified representations of thermodynamic properties that are typically employed in the fitting procedure were introduced to facilitate the application of constraints. The resulting model provides a consistent description of the thermodynamic properties of TMOS.

Vom Hühner-Holocaust über die Öko-Diktatur zum Kulturkampf um die Currywurst. Korpuslinguistische Perspektiven auf ernährungsbezogene Politisierungen - Markewitz, Friedrich; Wilk, Nicole M. (Zeitschrift für Literaturwissenschaft undLinguistik)

Brain complexity in motion: Multiscale entropy analysis on mobile EEG data to assess motor performance - Piskin, Daghan Yüksel; Cobani, Gjergji; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Brain Research Bulletin)

Zu Verbotenen Texten im Nationalsozialismus - Markewitz, Friedrich (Aptum. Zeitschrift für Sprachkritik und Sprachkultur)

Kommunikative Strategien im Umgang mit Macht und Ohnmacht im Getto Litzmannstadt - Markewitz, Friedrich (Macht und Partizipation in gesellschaftlichen Transformationsprozessen)

120 Tage im 'SS Experiment Love Camp'. Zu Genretropen und -kontroversen im Nazisploitationfilm - Markewitz, Friedrich (Pop-Zeitschrift)